IMPACT RANKINGS 2023 : Report Dmytro Motornyi Tavria State Agrotechnological University - (:unkn) unknown (TSATU, 2024)
In the face of adversity, the university continues to provide inclusive and high- quality education, supporting students, society, and scientific progress even under the most challenging conditions. Dmytro Motornyi Tavria State Agrotechnological University remains committed to advancing the Sustainable Development Goals, undeterred by the obstacles of war. Now, more than ever, our society needs collective efforts toward sustainable development, resilience, and the support of humanitarian initiatives. Despite the challenges of wartime, ensuring access to quality education for every student remains our highest priority. The University has developed support programmes for students and faculty who face hardships due to the war. Our educational programmes are adapted to ensure the continuity of the educational process even during crises, contributing to the training of highly qualified specialists equipped to rebuild and advance Ukraine's economy. The University continues to actively support gender equality as one of its fundamental values. In times of war, equality issues become especially significant, as many women are actively involved in the country’s recovery efforts, research, and educational initiatives. Energy independence and renewable energy sources have become extremely important for Ukraine. The University is engaged in green energy research, particularly in solar and bioenergy, which can ensure the energy stability of our country. We also equip students with the knowledge and skills needed to help rebuild Ukraine’s energy infrastructure according to sustainable development standards. Supporting decent work and economic growth is also a key area for the country. The University fosters partnerships with industries, enabling students to gain practical experience and supporting their professional development. Additionally, we are advancing research programs focused on developing new technologies in agriculture and food processing. We also contribute to developing digital infrastructure to ensure an uninterrupted educational process and support scientific work in the context of military operations. The university supports research aimed at protecting natural resources and rational land use, which is key to restoring the environment after war. Stability, peace, and justice are vital for Ukraine's reconstruction and prosperity. The University is working to create a safe, educational environment based on the principles of inclusiveness and support for the psychological health of students and faculty affected by the war. We believe that education can be a tool for building a peaceful society, so we actively promote the ideas of tolerance, justice, and mutual respect. The development of partnerships at the national and international levels is a key factor in achieving the goals of sustainable development in the face of current challenges. The University is strengthening its cooperation with other educational, scientific, and public organizations to address current issues and ensure continuous development together with partners. Participation in international projects and programs helps us not only to integrate best practices but also to attract resources for the development and support of our initiatives. Today, Dmytro Motornyi Tavria State Agrotechnological University remains a vital contributor to building a sustainable and equitable future for Ukraine. We are fully aware of the challenges we face. Yet, we firmly believe that by supporting the Sustainable Development Goals and fostering international cooperation, we can secure a promising future for generations to come.
IMPACT RANKINGS 2023 : ЗВІТ Таврійського державного агротехнологічного університету імені Дмитра Моторного
Keywords: Dmytro Motornyi Tavria State Agrotechnological University; Quality Education; Gender Equality; Decent Work and Economic Growth; Innovation and Infrastructure; Life on Land; Peace; Justice and Strong Institutions; Partnerships for the Goals; Sustainable Development Goals (SDGs)